Willingness to pay for watershed conservation at Hulu Langat, Malaysia - Mohamed, Norfashah (2013)
Watershed is the one of the many goods and services provided by tropical forests in Malaysia. Among the variety of watershed protection benefits, domestic water supply from watershed is crucial, particularly in Hulu Langat district. Hulu Langat watershed is one of the environment sensitive areas that need to be protected. This area supply domestic fresh water to the Hulu Langat communities. The essence of this study is to evaluate the economic benefit for conserving watersheds services to sustain domestic water supply at Hulu Langat, Selangor. This valuation is envisaged to yield the value of willingness to pay (WTP) of the communities for the conservation of the watershed. Besides, this study also intends to evaluate the communities‘ awareness towards watershed conservation. The contingent valuation method (CVM) was conducted to estimate communities‘ WTP for the conservation. The primary data obtained from questionnaire survey through personal interview. About 500 respondents have been interviewed in six sub districts that utilize water supply from Hulu Langat watershed area. In CVM, payment vehicle used was increment of monthly water bill of Hulu Langat communities for the proposed watershed conservation program. The questionnaire design was based on dichotomous choice format. The data analyses used was binary logit model to estimate the basic single bounded model and double bounded model. In this study, WTP relies on the socioeconomic variables which are bid amount, income, number of year attainment in education and residential area (urban or suburban) of the respondents. The results from single bounded model show that the communities are willing to pay RM10.13 per person monthly with mean WTP of 23.10 percent increment in monthly water bill per household. In double bounded dichotomous choice model, the results revealed that the mean WTP value is 19.25 percent increment in monthly water bill. Parallel to the WTP results, the communities also have awareness to protect the watershed for sustainable fresh water supply. Therefore, an increment in monthly water bill could be implemented in Hulu Langat district area to assist watershed conservation initiatives. Firm policies for conservation can be executed like reforestation, increase in regular patrol, monitoring activities in the forest and effective forest management to ensure reduction in illegal logging, forest fire and wildlife poaching.